Human Endogenous Retroviruses Are Preferentially Expressed in Mononuclear Cells From Cord Blood Than From Maternal Blood and in the Fetal Part of Placenta - Bergallo, Massimiliano; Marozio, Luca; Botta, Giovanni; Tancredi, Annalisa; Daprà, Valentina; Galliano, Ilaria; Montanari, Paola; Coscia, Alessandra; Benedetto, Chiara; Tovo, Pier Angelo (Frontiers in Pediatrics, 2020)
Background: Placenta shows high transcription levels of human endogenous retroviruses (HERVs) that are overexpressed during embryonic and fetal development. Methods: In order to gather further information on the degree of HERV activation in maternal and fetal tissues we assessed the transcription levels of pol genes of HERV-H, -K, and -W in PBMCs of newborns and their mothers as well as in chorion (fetal part) and decidua basalis (maternal part) of the placenta using a real time PCR assay. Results: Transcripts of pol genes of the three HERV families were significantly higher in mononuclear cells from cord blood than from maternal blood and in the fetal part than in the maternal part of the placenta. Conclusions: The HERV over-expressions in cells and tissues of the offspring are further clues that they play pivotal physiologic roles during early life events and suggest that HERV-driven abnormalities of pregnancy and fetal development should derive mostly from the conceptus, not from the mother.